A PUBLIC HEALTH PERSPECTIVE IN CRITICAL ANALYSIS OF THE ROLE OF RADIOLOGIC TECHNOLOGY IN NURSING. - 1Saleh Hamad Asker Lasloom, 2Mahdi Salem Ali Alyami, 3Hadi Saleh Nasser Alyami, 4Abdulhadi Hamad Askaralyami, 5Mohammed Saeed Saleh Alwadai, 6Salem Hamdan Mesfer Al Mukhles, 7Shaqraa Mosa Abdullah Majrashi, 8Ali Abdullah Dawwas Alyami, 9Dafer Hussain H; 10Fahaid Doghmel AwadA Lsaloom, 11Majed Ali Rashed Aliami, 12Mana Saad Al murdif (Chelonian Research Foundation, 2022)
This article analyses the part of innovation in patientcare from an open health perspective. Investigate the benefits, challenges, and moral contemplations of innovation in nursing. Through a comprehensive literature review this examination investigates current practices, evidence-based rules, and developing patterns utilizing open detailing. It moreover gives results from studies that assess the effect of radio on persistence. The discourse centered on the impact of radio innovation on open health, health justice, and well-being care aberrations. The article concludes with suggestions for utilizing quality radiologic devices in care to back open health objectives and guarantee quality care for all. Keywords: radiologic technology, nursing, public health, critical analysis, healthcare delivery, patient outcomes, health equity